Tax Officers' Work Harmony: The Role of Work-Life Balance and Mental Health - Hengky Pratama; Dielanova Wynni Yuanita; Rossalina Christanti (Owner : Riset dan Jurnal Akuntansi, 2025)
This research seeks to conduct an empirical investigation into the intrinsic factors affecting the performance of tax inspectors and account representatives, with particular emphasis on variables including work-life balance and mental health. The spillover theory provides the theoretical foundation for this investigation. The study's sample consists of tax officials stationed in Daerah Istimewa Yogyakarta, specifically those serving as tax inspectors and account representatives. Structural Equation Modeling-Partial Least Squares (SEM-PLS), implemented through the SmartPLS software, is utilized for various statistical analyses. This study employed purposive sampling as its methodological approach for participant selection. The findings of the study indicate that work-life balance does not exert a direct influence on the performance of tax inspectors and account representatives. However, the findings demonstrate that work-life balance positively influences mental health. Subsequently, enhanced mental health is associated with improved performance among tax inspectors and account representatives. This study provides a unique perspective by investigating the connection among work-life balance and the performance of tax inspectors and account representatives, mediated through mental health, and identifies significant positive outcomes. This research is essential in understanding how internal components influence the performance of tax inspectors and account representatives so that employees and the DGT, the agency where they work, can improve the performance of their personnel, so it can be a constructive suggestion and input for the human resources in DGT as the taxation authority if it wants to achieve the optimal target in tax revenue.